Malaysian culture can be a source of sustained competitive advantage for Malaysian organizations - Atta, Ebtehal; Yuserrie, Zainuddin (IJARW, 2019)
The current paper investigates the impact of organizational culture as a source of sustained competitive advantage to enhance performance in Malaysian organizations. Culture is a unique collection of values, beliefs, assumptions, and characters that determine how organizations manage their performance. This paper aims to reveal the influence of using new rules of (RBV) Rescores based view theory in applying Culture as a source of sustained competitive advantage to improve performance in Malaysian firms. In this sense, culture has pervasive effects on it, As the institutions in Malaysia are social institutions in social societies. The findings of this paper suggest that cultures can be a source of sustained competitive advantages in improving firm performance in Malaysian society.